Acceptability, safety, and patterns of use of oral pre-exposure prophylaxis to prevent HIV in healthy, South African adolescents - Gill, Katherine (Department of Public Health and Family Medicine, 2022)
Background: HIV incidence amongst adolescents in Southern Africa remains extremely high. The importance of adolescent HIV prevention strategies in tackling the epidemic worldwide is increasingly recognised with a global target from UNICEF to reduce new adolescent HIV infections by 75% by 2020. Adolescent vulnerability to HIV infection is a result of a complex interplay between structural, economic, socio-cultural, and biological factors during a phase when behaviours associated with HIV acquisition and sexual and reproductive health-seeking are initiated. The vulnerability of young people to HIV is particularly manifest in South Africa, where young women aged 15-24 accounted for almost 40% of new HIV infections in 2017. PreExposure Prophylaxis (PrEP) has been demonstrated to be effective for preventing HIV infection in adults but there is little data on its implementation among young people. Given the HIV incidence rates amongst adolescents in Southern Africa, oral PrEP for this group is likely to have an impact on population-level HIV incidence. We designed an open-label demonstration study known as Pluspills, for adolescents aged 15-19 years in South Africa to understand the safety, feasibility, and patterns of use of oral pre-exposure prophylaxis (PrEP) as part of a broad package of interventions, to prevent HIV. Methods: Pluspills was conducted in two distinct peri-urban settings in Johannesburg and Cape Town. The aim was to study the safety and acceptability of oral PrEP (tenofovir disoproxil fumarate/Emtricitabine) in two adolescent populations in South Africa. HIV-negative participants between 15-19 years old participated in an open-label oral PrEP study over 52 weeks. Participants took daily PrEP for the first 12 weeks and were then given the choice to opt-in or opt-out of PrEP use at three-monthly intervals. Serial plasma and DBS tenofovir concentrations were measured at every PrEP refill visit, and results were discussed with participants during adherence counselling sessions. Testing for sexually transmitted infections (STI's) was conducted at baseline, twelve and forty-eight weeks. Findings: Overall 148 participants were enrolled (median age 18 years; 67% female) and initiated PrEP. STI prevalence at the study start was high at 41% (60/148) and remained high throughout the study. The decision to stop using PrEP was made by 26 (18%) participants at 6 the 12-week visit. Cumulative PrEP opt-out at weeks 24 and 36 comprised 41% (60/148) and 43% (63/148) of the total cohort respectively. PrEP was relatively well tolerated with few reported adverse events. Tenofovir diphosphate (TFV-DP) levels as measured in dried blood spot samples were detectable (>16fmol/punch) in 92% (108/118)) of participants who reported PrEP use at week 12, 74% at week 24 (74/100), and 58% (22/37) by the end of the study. One HIV seroconversion occurred during the study (0.76/100 person-years) in a 19-yearold female participant who had chosen to stop taking PrEP, 24 weeks before diagnosis. Interpretation: In this small cohort of South African adolescents at risk of HIV acquisition, PrEP was safe and well-tolerated in those who continued to use it. PrEP use decreased throughout the study as visit frequency declined. The incidence of sexually transmitted infections remained high, despite low HIV incidence. The study confirms that this population needs access to PrEP with particular attention to tailored adherence support. Young people would also possibly benefit from the option for more frequent and flexible visit schedules.